2011
DOI: 10.5851/kosfa.2011.31.6.879
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analyses of Volatile Compounds in Cream Cheese and Cholesterol-removed Cream Cheese Made from Whole Milk Powder

Abstract: This study was to identify and quantify the flavor compounds in cream cheese and cholesterol-removed cream cheese made from whole milk powder stored at 7 o C for 4 wk. Flavor compounds of cream cheese were identified using gas chromatography mass spectroscopy and quantified by gas chromatography. The tentatively identified flavor compounds were mainly eight from fatty acids in cream cheese made from whole milk powder (CCWMP) and nine from fatty acids in cholesterol-removed cream cheese made from whole milk pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…In addition, the use of a time-of-flight mass spectrometer, followed by deconvolution of the signal obtained, enabled the extensive mapping of VOCs, which could explain the identification of many alkanes and alkenes in this study. Moreover, Jeon et al [51] observed that the acid group was the chemical class with the highest number of VOCs (HS-SPME) from cream cheeses. Thus, many alkanes and acids seem to be present in soft cheeses.…”
Section: Release Of Volatile Compounds 231 Vocs From the Processed Cr...mentioning
confidence: 99%
“…In addition, the use of a time-of-flight mass spectrometer, followed by deconvolution of the signal obtained, enabled the extensive mapping of VOCs, which could explain the identification of many alkanes and alkenes in this study. Moreover, Jeon et al [51] observed that the acid group was the chemical class with the highest number of VOCs (HS-SPME) from cream cheeses. Thus, many alkanes and acids seem to be present in soft cheeses.…”
Section: Release Of Volatile Compounds 231 Vocs From the Processed Cr...mentioning
confidence: 99%